Effectiveness of the Prof. Tito Storybook in Enhancing Student Learning in Indonesian Language and Natural Science for Fifth Grade Elementary School Students - Azima, Nana Fauzana; Iraqi, Hana Shilfia; Algifari, Arif; Zahra, Lailatul; Putri, Ellsy Rahmadani (Mimbar Sekolah Dasar, 2024)
This research addresses the issue of unsuitable children's storybooks influencing elementary students' thinking patterns by mirroring adult behaviors, prompting the development of the modern children's storybook "Prof. Tito: Electric Bicycle Edition" to enhance literacy and science technology education. The specific aim is to evaluate the effectiveness of character-based and science technology-focused storybooks in improving Indonesian and natural sciences learning among fifth-grade students. "Prof. Tito, Electric Bike Edition" explores values like cooperation, mutual assistance, and knowledge of electric bicycles, offering a moral foundation for young readers. The study highlights the storybook's role in fostering empathy and focus, while educating readers about electric bicycles in the context of Indonesian language and science. Through student evaluations, the book's efficacy was tested, showing significant learning improvements. The findings reveal a 13.49% and 12.55% increase in learning outcomes, classifying the storybook as moderately effective in enhancing learning. Overall, the research concludes that the storybook significantly contributes to improving student learning outcomes, representing an original contribution to the field.